Impairment of Autophagic Flux After Hypobaric Hypoxia Potentiates Oxidative Stress and Cognitive Function Disturbances in Mice - Shuhui Dai; Yuan Feng; Chuanhao Lu; Hongchen Zhang; Wenke Ma; Wenyu Xie; Xiuquan Wu; Peng Luo; Lei Zhang; Fei Fei; Zhou Fei; Xia Li (Neuroscience Bulletin, 2024)
Acute hypobaric hypoxic brain damage is a potentially fatal high-altitude sickness. Autophagy plays a critical role in ischemic brain injury, but its role in hypobaric hypoxia (HH) remains unknown. Here we used an HH chamber to demonstrate that acute HH exposure impairs autophagic activity in both the early and late stages of the mouse brain, and is partially responsible for HH-induced oxidative stress, neuronal loss, and brain damage. The autophagic agonist rapamycin only promotes the initiation of autophagy. By proteome analysis, a screen showed that protein dynamin2 (DNM2) potentially regulates autophagic flux. Overexpression of DNM2 significantly increased the formation of autolysosomes, thus maintaining autophagic flux in combination with rapamycin. Furthermore, the enhancement of autophagic activity attenuated oxidative stress and neurological deficits after HH exposure. These results contribute to evidence supporting the conclusion that DNM2-mediated autophagic flux represents a new therapeutic target in HH-induced brain damage.